Heterogeneously catalyzed two-step cascade electrochemical reduction of CO2 to ethanol. (1st June 2018) - Theaker, Nolan; Strain, Jacob M.; Kumar, Bijandra; Brian, J. Patrick; Kumari, Sudesh; Spurgeon, Joshua M.
Abstract: Electrochemical reduction of CO2 to liquid fuels is a promising route to a carbon-neutral, energy-dense storage of intermittent renewable electricity. However, electrocatalysts generally suffer from high overpotential and poor selectivity for multi-carbon products such as ethanol, and efforts to enhance such catalysts are limited by scaling relations which inhibit a simultaneous optimization of each elementary electrochemical step. In this work, the multistep proton-coupled electron-transfer reaction for the conversion of CO2 to C2 H5 OH was strategically divided into two independently optimized steps in a sequential cascade reaction using heterogeneous electrocatalysts to convert CO2 to CO and CO to C2 H5 OH within a single integrated electrochemical system. The exclusion of CO2 reactant from the second-stage electrolyzer was observed to be critical for maintaining appreciable ethanol selectivity. The cascade system produced C2 H5 OH at an overall faradaic efficiency of 11.0% at an average applied potential of −0.52 V vs. RHE, making it highly competitive with known single-step electrocatalysts for ethanol production from CO2 . This performance was despite limited conversion of the intermediate CO between cascade steps (∼6.4%), and reactor design improvements to enhance the conversion could lead to significantly enhanced ethanol production performance. Graphical abstract: Image 1